Population genetics of climbing perch, Anabas testudineus (Bloch, 1792) in the waters of Aceh Province, Indonesia - Nanda Muhammad Razi; Sri Riska Rahayu; Luvi Syafrida Handayani; Mutia Ramadhaniaty; Adrian Damora; Cut Tria Aswina; Putri Khairani Amalia Siregar; Nanda Ulfa Khaira; Muhammad Syukran; Puncak Joyontono; Muhammad Nasir; Nur Fadli; et al. (Ecological Genetics and Genomics, 2026)

Wind-driven Kelvin waves induce quasibiweekly oscillations in the coastal water of south Maritime Continent - Zhengpu Luo; Dwiyoga Nugroho; Adi Purwandana; Dezhou Yang; Zheng Wang; Rui Li; Xu Wang; Yuxuan Li; Priyadi Dwi Santoso; Muhammad Fadli; Bayu Priyono; Teguh Agustiadi; et al. (Deep Sea Research Part II: Topical Studies in Oceanography, 2026)

Indonesia's path to sustainable aviation fuel: Evaluating feedstock potential from agricultural residue - Afdal Adha; Muhammad Ilham Adhynugraha; Fithri Nur Purnamastuti; Fadli Cahya Megawanto; Budiyanto; Chairunnisa; Sherly Octavia Saraswati; Ilham Bagus Wiranto; Rinal Kharis; Indriasari; Fitrianto; Akhmad Amry; et al. (Biomass and Bioenergy, 2026)

Where waters transform: Hydrographic variability and turbulent mixing in the lifamatola passage, Indonesia - Adi Purwandana; Zheng Wang; Rui Li; Zhenhua Xu; Yao Li; Dewi Surinati; Fuad Azminuddin; Bayu Priyono; Dwiyoga Nugroho; Muhammad R. Cordova; Teguh Agustiadi; Mochamad R. Iskandar; et al. (Progress in Oceanography, 2026)

Morphometric and genetic variation of six soldierfish species (genus Myripristis, family: Holocentridae) harvested in Aceh Besar waters, Indonesia - Nadya Tirta; Essy Harnelly; Rania Feranita Fachri; Putri Khairani Amalia Siregar; Nanda Muhammad Razi; Nanda Ulfa Khaira; Mutia Ramadhaniaty; Sri Riska Rahayu; Nurlita Putri Anggraini; Raissha Amanda Siregar; Adrian Damora; Nur Fadli (Zoologischer Anzeiger, 2026)

Genetic Population of Rusty Jobfish Aphareus Rutilans (Cuvier, 1830), Including a New Sequence Record from South Aceh Waters Indonesia - Sri Riska Rahayu; Abdul Rahman Siregar; Mutia Ramadhaniaty; Nanda Muhammad Razi; Syamsul Rizal; Nur Fadli; Luvi Syafrida Handayani; Martin Wilkes; Mohd Nor Siti-Azizah; Su-fang Niu; Zainal Abidin Muchlisin (Thalassas: An International Journal of Marine Sciences, 2025)

DNA barcoding of fish from Singkil peat swamp waters of Aceh Province, Indonesia - Nanda Muhammad Razi; Sri Riska Rahayu; Luvi Syafrida Handayani; Nanda Ulfa Khaira; Muhammad Syukran; Ahmad Sazali A. Sitorus; Cut Tria Aswina; Putri Khairani Amalia Siregar; Muhammad Nasir; Nur Fadli; Martin Wilkes; Mohd Nor Siti-Azizah; et al. (Zoologischer Anzeiger, 2025)

Growth Patterns, Condition Factor, and Population Dynamics of Snapper Lutjanus bengalensis and Lutjanus lutjanus (Pisces: Lutjanidae) Harvested from Aceh Waters Indonesia - Sri Riska Rahayu; Syamsul Rizal; Nur Fadli; Ilham Raza; Muhammad Isran Lazuardi; Luvi Syafrida Handayani; Nanda Muhammad Razi; Martin Wilkes; Mohd Nor Siti-Azizah; Zainal A. Muchlisin (Thalassas: An International Journal of Marine Sciences, 2024)

Vertical distribution of microplastic along the main gate of Indonesian Throughflow pathways - Corry Yanti Manullang; Mufti Petala Patria; Agus Haryono; Sabiqah Tuan Anuar; Muhammad Fadli; Raden Dwi Susanto; Zexun Wei (Marine Pollution Bulletin, 2024)

Prediction of extreme rain in Kototabang using Himawari-8 satellite based on differences in cloud brightness temperature - Nining Jumianti; Marzuki Marzuki; Helmi Yusnaini; Ravidho Ramadhan; Wendi Harjupa; Elfira Saufina; Fadli Nauval; Risyanto Risyanto; Anjar Dimara Sakti; Muhammad Rais Abdillah; Prasanti Widyasih Sarli (Remote Sensing Applications: Society and Environment, 2024)

Morphometric and genetic variations of three grouper species (genus Epinephelus) from the northern region of Aceh province, Indonesia - Nur Fadli; Adrian Damora; Zainal Abidin Muchlisin; Mutia Ramadhaniaty; Nanda Muhammad Razi; Sri Riska Rahayu; Edison D. Macusi; Ahasan Habib; Mohd N. Siti-Azizah (Zoologischer Anzeiger, 2023)

Morphometric and genetic variations of four dominant species of snappers (Lutjanidae) harvested from the Northern Coast of Aceh waters, Indonesia - Sri Riska Rahayu; Zainal A. Muchlisin; Nur Fadli; Nanda Muhammad Razi; Mutia Ramadhaniaty; Luvi Syafrida Handayani; Siti Maulida; Firman M. Nur; Nurlaili Nurlaili; Moh N. Siti-Azizah (Zoologischer Anzeiger, 2023)

Why do people visit primate tourism sites? Investigating macaque tourism in Japan and Indonesia - Asmita Sengupta; Kanthi Arum Widayati; Yamato Tsuji; Risma Yanti; Muhammad Fadli Rahman; Nagarathna Balakrishna; Sindhu Radhakrishna (Primates, 2021)

Changes in extreme temperature and precipitation in the Arab region: long‐term trends and variability related to ENSO and NAO - M. G. Donat; T. C. Peterson; M. Brunet; A. D. King; M. Almazroui; R. K. Kolli; Djamel Boucherf; Anwar Yousuf Al‐Mulla; Abdourahman Youssouf Nour; Ahmed Attia Aly; Tamer Ali Ali Nada; Muhammad M. Semawi; et al. (International Journal of Climatology, 2014)
A workshop was held in Casablanca, Morocco, in March 2012, to enhance knowledge of climate extremes and their changes in the Arab region. This workshop initiated intensive data compilation activities of daily observational weather station data from the Arab region. After conducting careful control processes to ensure the quality and homogeneity of the data, climate indices for extreme temperatures and precipitation were calculated. This study examines the temporal changes in climate extremes in the Arab region with regard to long‐term trends and natural variability related to ENSO and NAO . We find consistent warming trends since the middle of the 20th Century across the region. This is evident in the increased frequencies of warm days and warm nights, higher extreme temperature values, fewer cold days and cold nights and shorter cold spell durations. The warming trends seem to be particularly strong since the early 1970s. Changes in precipitation are generally less consistent and characterised by a higher spatial and temporal variability; the trends are generally less significant. However, in the western part of the Arab region, there is a tendency towards wetter conditions. In contrast, in the eastern part, there are more drying trends, although, these are of low significance. We also find some relationships between climate extremes in the Arab region and certain prominent modes of variability, in particular El Niño‐Southern Oscillation ( ENSO ) and North Atlantic Oscillation ( NAO ). The relationships of the climate extremes with NAO are stronger, in general, than those with ENSO , and are particularly strong in the western part of the Arab region (closer to the Atlantic Ocean). The relationships with ENSO are found to be more significant towards the eastern part of the area of study. © 2013 Royal Meteorological Society

Why was the 2008 Indian Ocean Dipole a short-lived event? - Iskhaq Iskandar; Muhammad Irfan; Fadli Saymsuddin (Ocean Science Journal, 2013)